MESUA FERREA LINN. (NAGKESAR): A POTENT ANTIMICROBIAL PLANT SPECIES - THAKUR, SHIFALI; KAURAV, HEMLATA; CHAUDHARY, GITIKA (International Journal of Current Pharmaceutical Research, 2021)
Many plants have not been investigated thoroughly, which are used traditionally as a medicine to cure various diseases. Herbal plants play a vital role in the development of new drugs which can be used for various therapeutic indications. Mesua ferrea linn., commonly known as 'Nagchampa' or 'Nagkesar', is one such herbal plant having many potential therapeutic activities. It is used in diseases like rheumatism, asthma, inflammation, fever, dyspepsia, renal diseases, dysentery, bleeding piles, a bacterial and fungal infection. This plant possesses many bioactive chemical constituents like coumarins, xanthones, pyranoxanthones, flavonoids, terpenoids and steroids which can be easily isolated. It can act as precursors on many ailments. These bioactive constituents have many pharmacological activities such as anticancer, antimicrobial, antifungal, anti-inflammatory, anti-arthritis, analgesic, diuretic, anti-hemorrhoid, antiulcer and many more. Almost every part of the plant is reported to have beneficial medicinal properties. But further studies are still needed to explore the pharmacological activities of Mesua ferrea linn. plant so as to gain benefit for the treatment of various diseases. This review highlights the general description, phytochemical profiling, traditional uses and proven pharmacological attributes of Mesua ferrea linn. plant.